Live and die with dignity - Spahic, Omer (islamicity.org, 2018)
So difficult and complex is the predicament of Muslims nowadays that it, perhaps, has no equal in history. The problems and challenges are ubiquitous and global in character, encompassing all aspects of life. However, the most critical and so, most systematically targeted are such aspects as are related to spirituality, morality and education. The much-talked-about notions of Muslim unity, culture, economy and politics are but corollaries of the former. There are many entities in the world which seem to be happy only when Muslims are kept ignorant, divided, disoriented, subdued and when they shed each other’s blood. To them, it is almost an international crime if a Muslim nation becomes genuinely independent, visionary and start doing well (the recent dramatic and hardly fathomable economic troubles in Turkey are the case in point). To them, furthermore, it is a convention that Muslims should be perennially impoverished and needy, depending on their support and wherewithal. Muslims and their countries are to be turned into the dumping grounds for such people’s cultural, intellectual, military and industrial leftovers, and in the worst-case scenario, outright waste. Muslims are to dominate the news for all the wrong reasons. The dark side of history is to be inscribed predominantly by Muslims and their societies. Hence, the only way forward for Muslims would be in following especially the West and its cultural and civilizational model. It is there that the end-point of humanity’s sociocultural evolution and the final form of human government will come to pass. As a political and philosophical concept, the “end of history” has thus been increasingly articulated.